Perception of Generation Z towards Leadership in the Workplace (A Study at HIJ Company) - Nugraha, Fajar; Prasetyo, Baskhoro Edo; Sugiarti, Rini; Suhariadi, Fendy (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study investigates Generation Z's perceptions of workplace leadership, emphasizing the core dimensions of Self-Determination Theory (SDT): autonomy, competence, and relatedness. The research aims to explore how these dimensions influence job satisfaction, motivation, and engagement among Generation Z employees. Through qualitative interviews, the study examines how individuals view leadership that promotes autonomy, challenges their capabilities, and nurtures meaningful relationships. The findings reveal that Generation Z highly values autonomy, feeling more motivated and trusted when granted the freedom to make decisions. Competence also emerges as a significant factor, with participants favoring tasks that test their abilities and constructive feedback that supports their growth. Additionally, the relatedness dimension proves crucial, as employees feel more engaged and loyal to leaders who understand their personal aspirations and cultivate inclusive, supportive environments. These insights carry important implications for leadership practices, suggesting that effective leaders should empower employees by fostering autonomy, providing opportunities for development, and building strong interpersonal connections. The results offer valuable contributions to understanding how to successfully manage and motivate Generation Z in the modern workplace.